Ciltacabtagene autoleucel, a B-cell maturation antigen-directed chimeric antigen receptor T-cell therapy in patients with relapsed or refractory multiple myeloma (CARTITUDE-1): a phase 1b/2 open-label study. Issue 10297 (24th July 2021) - Berdeja, Jesus G; Madduri, Deepu; Usmani, Saad Z; Jakubowiak, Andrzej; Agha, Mounzer; Cohen, Adam D; Stewart, A Keith; Hari, Parameswaran; Htut, Myo; Lesokhin, Alexander; Deol, Abhinav; Munshi, Nikhil C; et al.
Summary: Background: CARTITUDE-1 aimed to assess the safety and clinical activity of ciltacabtagene autoleucel (cilta-cel), a chimeric antigen receptor T-cell therapy with two B-cell maturation antigen-targeting single-domain antibodies, in patients with relapsed or refractory multiple myeloma with poor prognosis. Methods: This single-arm, open-label, phase 1b/2 study done at 16 centres in the USA enrolled patients aged 18 years or older with a diagnosis of multiple myeloma and an Eastern Cooperative Oncology Group performance status score of 0 or 1, who received 3 or more previous lines of therapy or were double-refractory to a proteasome inhibitor and an immunomodulatory drug, and had received a proteasome inhibitor, immunomodulatory drug, and anti-CD38 antibody. A single cilta-cel infusion (target dose 0·75 × 10 6 CAR-positive viable T cells per kg) was administered 5–7 days after start of lymphodepletion. The primary endpoints were safety and confirmation of the recommended phase 2 dose (phase 1b), and overall response rate (phase 2) in all patients who received treatment. Key secondary endpoints were duration of response and progression-free survival. This trial is registered with ClinicalTrials.gov, NCT03548207 . Findings: Between July 16, 2018, and Oct 7, 2019, 113 patients were enrolled. 97 patients (29 in phase 1b and 68 in phase 2) received a cilta-cel infusion at the recommended phase 2 dose of 0·75 × 10 6 CAR-positive viable T cells per kg. As of the Sept 1, 2020 clinical cutoff, median follow-up was 12·4 months (IQR 10·6–15·2). 97 patients with a median of six previous therapies received cilta-cel. Overall response rate was 97% (95% CI 91·2–99·4; 94 of 97 patients); 65 (67%) achieved stringent complete response; time to first response was 1 month (IQR 0·9–1·0). Responses deepened over time. Median duration of response was not reached (95% CI 15·9–not estimable), neither was progression-free survival (16·8–not estimable). The 12-month progression-free rate was 77% (95% CI 66·0–84·3) and overall survival rate was 89% (80·2–93·5). Haematological adverse events were common; grade 3–4 haematological adverse events were neutropenia (92 [95%] of 97 patients), anaemia (66 [68%]), leukopenia (59 [61%]), thrombocytopenia (58 [60%]), and lymphopenia (48 [50%]). Cytokine release syndrome occurred in 92 (95%) of 97 patients (4% were grade 3 or 4); with median time to onset of 7·0 days (IQR 5–8) and median duration of 4·0 days (IQR 3–6). Cytokine release syndrome resolved in all except one with grade 5 cytokine release syndrome and haemophagocytic lymphohistiocytosis. CAR T-cell neurotoxicity occurred in 20 (21%) patients (9% were grade 3 or 4). 14 deaths occurred in the study; six due to treatment-related adverse events, five due to progressive disease, and three due to treatment-unrelated adverse events. Interpretation: A single cilta-cel infusion at the target dose of 0·75 × 10 6 CAR-positive viable T cells per kg led to early, deep, and durable responses in heavily pretreated patients with multiple myeloma with a manageable safety profile. The data from this study formed the basis for recent regulatory submissions. Funding: Janssen Research & Development and Legend Biotech.